A dielectric model of thawed and frozen Arctic organic soils at 435 MHz. Issue 5 (4th May 2022) - Savin, Igor V.; Muzalevskiy, Konstantin V.; Mironov, Valery L.
ABSTRACT: A refractive-mixing dielectric model for frozen and thawed organic-rich soils at a frequency of 435 MHz was developed in this letter. The model was developed based on the dielectric measurements of five soil samples in which organic matter content was variated from 35% to 80% (by weight). Dielectric measurements were conducted in the range of volumetric soil moisture from 2% to 60%, and the range of temperature from −30°C to 25°C. Coefficient of determination (R 2 ) and root mean square error (RMSE) between predicted by the model and measured values for real ( ε ′ ) and imaginary ( ε ′ ′ ) part of complex relative permittivity are R ε ′ 2 = 0.989 ( R M S E ε ′ =0.602) and R ε ′ ′ 2 = 0.906 ( R M S E ε ′ ′ =0.404), respectively. The developed dielectric model can be used for creating remote sensing algorithms (soil moisture retrieval in the root zone, active layer thickness and ice content measuring in permafrost area, etc.) in P-band.